2012
DOI: 10.1021/ct300887t
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo Study of π-Bonded Transition Metal Organometallics: Neutral and Cationic Vanadium–Benzene and Cobalt–Benzene Half Sandwiches

Abstract: We present accurate quantum Monte Carlo (QMC) calculations that enabled us to determine the structure, spin multiplicity, ionization energy, dissociation energy, and spin-dependent electronic gaps of neutral and positively charged vanadium-benzene and cobalt-benzene systems. From total/ionization energy, we deduce a sextet (quintet) state of neutral (cationic) vanadium-benzene systems and quartet (triplet) state of the neutral (cationic) cobalt-benzene systems. Vastly different energy gaps for the two spin cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…Previous DFT and WF-based computational studies [30,31,54] have identified the hollow site as being a stable binding site for cobalt on the substrate, although some experimental studies show evidence of binding at the top site as well [55]. Here, we focus on modelling the hollow-site complex because one key aim of this work is to assess the reliability of previous calculations.…”
Section: Interaction Of Cobalt and Benzenementioning
confidence: 99%
See 1 more Smart Citation
“…Previous DFT and WF-based computational studies [30,31,54] have identified the hollow site as being a stable binding site for cobalt on the substrate, although some experimental studies show evidence of binding at the top site as well [55]. Here, we focus on modelling the hollow-site complex because one key aim of this work is to assess the reliability of previous calculations.…”
Section: Interaction Of Cobalt and Benzenementioning
confidence: 99%
“…These systems typically have many neardegenerate states, and may show strong electron-correlation effects. Approximate DFT descriptions of cobalt approaching a graphene model can be strongly functional dependent [29,30], and correlated wavefunction-based methods are probably needed to accurately analyse the energetics of such systems. Although wavefunction-based methods can provide a more consistent description [30,31], the computational costs typically rise very quickly with system size.…”
Section: Introductionmentioning
confidence: 99%
“…47,[51][52][53][54] Modern massively parallel computers have expanded the applicability of QMC methods not only to larger molecular systems but also to periodic systems because of their high parallel efficiency. 55,56 One of the most practical QMC methods, fixed-node diffusion Monte Carlo (FN-DMC), has been applied to noncovalent molecular systems and demonstrated to have an accuracy comparable to CCSD(T).…”
Section: Introductionmentioning
confidence: 99%
“…55,56 One of the most practical QMC methods, fixed-node diffusion Monte Carlo (FN-DMC), has been applied to noncovalent molecular systems and demonstrated to have an accuracy comparable to CCSD(T). 47,[51][52][53][54] Since the accuracy of FN-DMC depends critically on the choice of trial nodal surface, one should take care when generating this surface. If one uses DFT, experience shows that the nodal structures generally depend on the functional employed, and many choices are available in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this possibility is worth investigating, particularly in the light of recent remarkable improvements in the QMC technology and quality of the results that can routinely be obtained (see Refs. [37][38][39][40][41][42][43][44][45][46] for representative examples).…”
Section: Introductionmentioning
confidence: 99%